Formulasi dan Evaluasi Sediaan Serbuk Effervescent Ekstrak Daun Kelor (Moringa oleifera L.) - Ririn Rodhatul Janah; Annisaur Rohmi Saadah; Anika Putri Rahmadani; Apriliya Yogi Murawalin; Helga Delferis Ayu Erlesya (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2025)
Moringa leaves contain the substance β-sitosterol which is an efficacious component for treating allergies, aches and pains, rheumatism, infected wounds, lowering blood sugar and uric acid levels and even lowering blood pressure. Moringa leaves can reduce systolic/diastolic blood pressure with a value of 153/94 to 129/86. Extracted Moringa leaves can be processed in the form of tablets, capsules and powder. The aim of this research is to obtain a good Moringa leaf effervescent powder formula based on physical evaluation of the preparation (organoleptic test, water content test, pH test, flow time, angle of repose and depression time). There are 3 formulas with component ratios of tartaric acid, sodium bicarbonate and CMC-Na as follows: formula I (1:1), formula II (1.2:1), formula III (1:..:1). This type of research is quantitative descriptive research. The results of the research show that of the three preparation formulas for Moringa leaf extract effervescent powder which has the best physical test is formula I. Formulation I in the organoleptic test, the powder is white, has a distinctive sweet smell and sweet taste, the water content on the Moisture Analyzer tool for 3.15 minutes is obtained yield 2.56%, acidity level (Ph) 4-5, flow rate 4.98 seconds, and dispersion time Keywords: Moringa leaves, effervescent powder, physical test.